Integration of Local Wisdom and Islamic Education in The Batimung Ritual of the Banjarese Community - Sheila Rosalia; Nuril Khasyi'in; Mutia Rahmawati; Reza Setya Rachman (Values: Jurnal Kajian Islam Multidisiplin, 2026)
Batimung is a traditional steam-bathing ritual practiced by the Banjar community that continues to be preserved, particularly in the contexts of marriage and traditional health care. This tradition functions not only as a form of physical treatment but also embodies spiritual and social values rooted in Islamic teachings. Nevertheless, many people especially younger generations tend to perceive Batimung merely as a beauty or health treatment, without fully understanding its educational and religious significance. This study aims to examine the integration of local wisdom and Islamic educational values embedded in the Batimung tradition within Banjar society. Employing a qualitative descriptive approach, data were collected through in-depth interviews and field observations involving Batimung practitioners in Panggung Baru Village, Tanah Laut Regency, supported by relevant literature review. The findings reveal that Batimung contains Islamic educational values such as thaharah (purity), faith, health preservation, cooperation (ta‘awun), and gratitude, which function as informal educational media grounded in local culture. This study highlights that Batimung is not merely a cultural heritage, but also a culturally embedded educational practice that remains relevant for moral and spiritual character formation within the Banjar community amid the challenges of modernization.